Pengaruh Penyuluhan Gizi terhadap Pengetahuan Kader dan Ibu Balita dalam Pemanfaatan Tepung Lele dan Tepung Labu Kuning untuk Pencegahan Stunting - Elsyie Yuniarti; Sri Darningsih; Ismanilda Ismanilda; Renita Afriza; Kasmiyeti Kasmiywti; Safyanti Safyanti (Poltekkes Kemenkes Padang, 2026)
Stunting remains a public health problem in Indonesia, with a prevalence of 19.8% in 2024. Although local foods have the potential to support stunting prevention, the knowledge of Posyandu cadres and mothers of under-five children regarding the utilization of protein- and vitamin A-rich local foods, such as catfish flour and pumpkin flour, is still limited. This study aimed to determine the effect of nutrition education on the knowledge of Posyandu cadres and mothers of under-five children regarding the utilization of catfish flour and pumpkin flour for stunting prevention. This study employed a pre-experimental design with a one-group pretest-posttest approach. The population consisted of Posyandu cadres and mothers of under-five children in the working area of Andalas Public Health Center. A total of 64 participants were selected using the Federer formula and a multistage random sampling technique. Data were analyzed using the paired t-test. The instrument used was a pretest and posttest questionnaire to measure the knowledge levels of Posyandu cadres and mothers of under-five children. The results showed that nutrition education supported by audiovisual media and hands-on practice improved the knowledge of Posyandu cadres and mothers of under-five children regarding the utilization of local foods for stunting prevention, as indicated by a p-value ≤ 0.05, although not all groups demonstrated significant changes. This intervention may serve as a supportive strategy to accelerate stunting reduction through Posyandu activities.